(untitled) (Bangladesh Journal of Pharmacology, 2011)
This study was conducted to investigate the anti-Plasmodium berghei activities of some extracts from Indigofera pulchra leaves. Six groups of mice were intraperitoneally infected with chloroquine sensitive P. berghei (NK 65) among which two groups were orally treated with 100 and 200 mg/kg body weight of methanol leaves extract while another two groups were treated with 100 and 200 mg/kg of n-butanol fraction derived from the methanol extract. Another infected group was treated with chloroquine (25 mg/kg) whereas the remaining infected group was left untreated. All infected treated groups possessed a significantly (p<0.05) lowered number of parasitized erythrocytes than the infected untreated group throughout the experimental period except at day 6 post-infection. However, the 200 mg/kg n-butanol fraction treated group demonstrated a persistently lower number of parasitized erythrocytes than other extract-treated groups after day 9 post infection to the termination of the experiment. The P. berghei was found to induce anemia whose severity was significantly (p<0.05) ameliorated by all the treatments. It was concluded that the methanol extract and n-butanol fraction of I. pulchra contains anti-P. berghei phytochemicals that could ameliorate the parasite-induced anemia.